Reductant

The reducing agent, comprising an oxygen carrier with oxygen ion conductivity and latent heat storage particles, addresses the temperature-related challenges in chemical looping methods by stabilizing reaction temperatures and enhancing the efficiency of carbon dioxide conversion to carbon monoxide.

JP2025051572APending Publication Date: 2025-04-04SEKISUI CHEMICAL CO LTD +1

Patent Information

Application Number
JP2024022484
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-02-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Chemical looping methods for converting carbon dioxide to carbon monoxide face challenges due to temperature swings caused by exothermic and endothermic reactions, leading to performance and life deterioration of oxygen carriers and making heat control difficult.

Method used

A reducing agent is developed that includes an oxygen carrier with oxygen ion conductivity and latent heat storage particles. The oxygen carrier contains metal elements from Groups 3 and 4 of the periodic table, and the latent heat storage particles have core particles with a melting point of 100°C or higher, coated with materials that do not react with the core particles at operating temperatures, to absorb and store reaction heat.

Benefits of technology

The reducing agent effectively suppresses the deterioration of oxygen carrier performance and life, simplifies thermal control, and enhances the efficiency of carbon dioxide conversion to carbon monoxide by stabilizing reaction temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051572000001_ABST
    Figure 2025051572000001_ABST
Patent Text Reader

Abstract

To provide a reductant capable of preventing or suppressing deterioration in performance and lifespan of an oxygen carrier while enabling relatively easy thermal control.SOLUTION: According to one aspect of the present invention, a reductant is provided which generates oxygen defects upon contact with a reducing gas containing hydrogen and eliminates the oxygen defects upon contact with an oxidizing gas containing carbon dioxide. The reductant contains an oxygen carrier having oxygen ion conductivity and latent heat storage particles. The oxygen carrier includes at least two metal elements belonging to Group 3 and Group 4 of the periodic table, including lanthanoids and actinoids, or includes Fe. The latent heat storage particles comprise a core particle and a coating part covering at least a portion of the core particle. The core particle is composed of an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound mainly composed of the element, having a melting point of 100°C or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reducing agent, and more particularly to a reducing agent that can be used, for example, in a chemical looping method. [Background technology]

[0002] In recent years, the concentration of carbon dioxide, a type of greenhouse gas, in the atmosphere has been increasing. The increase in the concentration of carbon dioxide in the atmosphere contributes to global warming. Therefore, it is important to capture carbon dioxide emitted into the atmosphere, and if the captured carbon dioxide can be converted into carbon valuables and reused, a carbon circulation society can be realized. Conventionally, a method utilizing the reverse water-gas shift reaction has been known as a method for producing carbon monoxide from carbon dioxide. However, this conventional reverse water-gas shift reaction has a problem in that the conversion efficiency (yield) of carbon dioxide to carbon monoxide is low due to the constraints of chemical equilibrium because the products, carbon monoxide and water, coexist in the system.

[0003] In order to solve the above problems, carbon dioxide is converted (synthesized) into carbon monoxide by using a chemical looping method (see Patent Document 1). The chemical looping method referred to here is a method in which the reverse water gas shift reaction is divided into two reactions, a reduction reaction with hydrogen and a production reaction of carbon monoxide from carbon dioxide, and these reactions are carried out in the presence of an oxygen carrier (e.g., a metal oxide: MO x ) to bridge the gap (see formula below). H 2 +MO x → H 2 O + MO x-1 CO 2 +MO x-1 → CO + MO x In the above formula, MO x-1 indicates a state in which the metal oxide is partially or completely reduced.

[0004] In such a chemical looping method, since water and carbon monoxide, which are substrates for the reverse reaction, do not coexist during each reaction, it is possible to obtain a higher conversion efficiency of carbon dioxide to carbon monoxide than the chemical equilibrium of the reverse water gas shift reaction. As an oxygen carrier used in this chemical looping reaction, a method using a composite metal oxide containing cerium oxide is known. For example, Patent Document 1 describes a method using cerium oxide containing zirconium. Also, Patent Document 2 describes a method using a reducing agent in which an oxygen carrier is molded to have predetermined physical properties and structure in order to make it difficult to increase the gas passage resistance during the chemical looping reaction.

[0005] However, in the chemical looping reaction, the reduction reaction of the oxygen carrier is a reaction that releases oxygen element from the oxygen carrier, while the conversion reaction of carbon dioxide to carbon monoxide is a reaction that supplies (absorbs) oxygen element to the oxygen carrier, so the oxygen carrier repeats exothermic and endothermic reactions. For example, when cerium oxide is used as the oxygen carrier, the conversion reaction of hydrogen to water is an endothermic reaction, and the conversion reaction of carbon dioxide to carbon monoxide is an exothermic reaction. For this reason, a temperature swing occurs in the reaction vessel due to the effect of the reaction heat of the oxygen carrier, so the performance and life of the oxygen carrier are likely to decrease, and the heat control process becomes difficult. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5858926 [Patent Document 2] Patent Publication No. 2021-49489 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above circumstances, the present invention provides a reducing agent which prevents or suppresses the deterioration of the performance and life of the oxygen carrier and allows heat control to be performed relatively easily. [Means for solving the problem]

[0008] According to one aspect of the present invention, there is provided a reducing agent which generates oxygen vacancies by contact with a reducing gas containing hydrogen and which eliminates the oxygen vacancies by contact with an oxidizing gas containing carbon dioxide. The reducing agent contains an oxygen carrier having oxygen ion conductivity and latent heat storage particles. The oxygen carrier contains at least two of the metal elements belonging to Groups 3 and 4 of the periodic table, including lanthanides and actinides, or contains Fe. The latent heat storage particles have a core particle and a coating portion that coats at least a part of the core particle. The component of the core particle is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound mainly containing the element, and has a melting point of 100°C or higher. The components of the coating portion do not react with the core particles or have poor reactivity with the core particles in the temperature range of the operating temperature of the reducing agent, are different from the components of the core particles, and are at least one selected from the group consisting of elements, alloys and inorganic compounds containing the elements, and mixtures thereof. The content of the latent heat storage particles in the reducing agent is 1% by mass or more and 60% by mass or less. The crushing strength of the reducing agent is 1 N or more and 40 N or less. The bulk density of the reducing agent is 0.1 g / cm 3 More than 5g / cm 3 The cumulative specific surface area of ​​the reducing agent measured by pore size distribution measurement using a mercury intrusion method using a mercury porosimeter is 3 m or less. 2 / g or more, and the cumulative pore volume is 0.1 cm 3 / g or more.

[0009] According to this embodiment, deterioration in the performance and life of the oxygen carrier can be prevented or suppressed, and heat control can be performed relatively easily. [Brief description of the drawings]

[0010] [Figure 1] This is a scanning electron microscope (SEM) image of latent heat storage particles. [Diagram 2]These are the results of measurements of latent heat storage particles using X-ray diffraction (XRD). [Diagram 3] These are the results of measurement of latent heat storage particles by differential scanning calorimetry (DSC). [Figure 4] 1 is a photograph showing the appearance of the reducing agents obtained in Examples 1 and 2. [Diagram 5] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 6] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 7] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 8] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 9] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 10] These are the measurement results of the reducing agent by X-ray diffraction (XRD). [Figure 11] 2 shows a scanning electron microscope (SEM) image and an element mapping image of a cross section along the thickness direction of the reducing agent obtained in Example 2. [Figure 12] 1 is a scanning electron microscope (SEM) image of a cross section along the thickness direction of the reducing agent obtained in Example 2. [Figure 13] 1 is a scanning electron microscope (SEM) image of a cross section along the thickness direction of the reducing agent obtained in Comparative Example 1. [Figure 14] FIG. 1 is a conceptual diagram showing the configuration of a device (reactor 1) for evaluating the temperature change of a reducing agent. [Figure 15] FIG. 2 is a conceptual diagram showing the configuration of a device (reactor 2) for evaluating the temperature change of a reducing agent. [Figure 16] 1 is a graph showing the evaluation results of temperature changes of the reducing agents obtained in Example 1, Reference Example 1, and Reference Example 2. [Figure 17] 1 is a graph showing the evaluation results of the temperature change of the reducing agents obtained in Example 2, Reference Example 3, and Reference Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The reducing agent of the present invention will be described in detail below based on preferred embodiments. The reducing agent of the present embodiment has the property of generating oxygen vacancies when in contact with a reducing gas containing hydrogen, and of eliminating the oxygen vacancies when in contact with an oxidizing gas containing carbon dioxide. In this case, preferably, a reducing gas and an oxidizing gas are passed alternately through a reaction tube (reaction vessel) filled with a reducing agent, whereby carbon dioxide is converted to carbon monoxide by the reducing agent, and the reducing agent in an oxidized state is regenerated by the reducing gas (hydrogen is converted to water).

[0012] The reducing agent contains an oxygen carrier having oxygen ion conductivity and latent heat storage particles. As a result, when a composite metal oxide containing cerium oxide is used as the oxygen carrier, during the hydrogen to water conversion reaction (endothermic reaction) by the oxygen carrier, the core particles of the latent heat storage particles change from a liquid phase to a solid phase to provide the oxygen carrier with latent heat (coagulation heat) and during the carbon dioxide to carbon monoxide conversion reaction (exothermic reaction), the core particles of the latent heat storage particles change from a solid phase to a liquid phase to absorb and store the heat generated by the oxygen carrier. This reduces the temperature change of the reducing agent (oxygen carrier), thereby suppressing the deterioration of the performance and life of the oxygen carrier. Furthermore, because the temperature change of the reducing agent is reduced, the thermal energy input to the reducing agent from the outside can also be reduced, and therefore the temperature control (heat control) of the reducing agent can also be easily simplified.

[0013] <Oxygen Carrier> An oxygen carrier is a compound that can cause reversible oxygen deficiency; it loses oxygen element by reduction itself, but when it comes into contact with carbon dioxide in an oxygen-deficient state (reduced state), it acts to remove the oxygen element from the carbon dioxide and reduce it. The oxygen carrier in this embodiment contains at least two of the metal elements belonging to Groups 3 and 4 of the periodic table, including lanthanides and actinides, or contains Fe. In such an oxygen carrier, the crystal lattice is distorted by containing two or more metal elements or by containing Fe, and oxygen element is smoothly transferred between the oxygen carrier and a counter substance (e.g., carbon dioxide, hydrogen). Therefore, the conversion efficiency from carbon dioxide to carbon monoxide and the conversion efficiency from hydrogen to water can be improved.

[0014] Examples of metal elements belonging to Groups 3 and 4 include scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), samarium (Sm), gadolinium (Gd), titanium (Ti), zirconium (Zr), hafnium (Hf), etc. The oxygen carrier may contain only two types of the above metal elements, or may contain three or more types, or may contain four or more types. Among these, the oxygen carrier preferably contains Ce and Zr, or contains Fe. The oxygen carrier containing Ce and Zr, or Fe, is more likely to cause distortion in the crystal lattice, and more smoothly transfers oxygen elements between the oxygen carrier and the counter substance. The oxygen carrier may contain metal elements belonging to Group 3 and Group 4, or elements other than Fe. Examples of the other elements include niobium (Nb), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), indium (In), gallium (Ga), and bismuth (Bi). The reactivity of the oxygen carrier can be adjusted by adding these other elements.

[0015] <How to prepare oxygen carrier> The method for producing the oxygen carrier is not particularly limited, but examples thereof include the sol-gel method, co-precipitation method, solid phase method, and hydrothermal synthesis method. As an example, the oxygen carrier can be produced as follows. First, a salt of a metal element constituting the oxygen carrier is dissolved in water to prepare an aqueous solution. Next, the aqueous solution is heated to gel, and then dried and baked. That is, the oxygen carrier can be produced easily and reliably by the so-called sol-gel method. In addition, for preparing the aqueous solution, acidic water adjusted to be acidic with, for example, citric acid, acetic acid, malic acid, tartaric acid, hydrochloric acid, nitric acid, or a mixture thereof may be used.

[0016] Examples of the salt of a metal element include nitrates, sulfates, chlorides, hydroxides, carbonates, and compounds thereof, among which nitrates are preferred. Furthermore, hydrates of the salt of a metal element may be used as necessary. The gel is dried at a temperature of preferably 20° C. to 200° C., more preferably 50° C. to 150° C., for a time of preferably 0.5 to 20 hours, more preferably 1 to 15 hours. By drying in this manner, the gel can be dried uniformly.

[0017] The gel is preferably fired at a temperature of 300°C to 1200°C, more preferably 700°C to 1000°C, for a time of 1 hour to 24 hours, more preferably 1.5 hours to 20 hours. The gel is preferably converted into an oxide by firing, but can be easily converted into an oxygen carrier by firing under the above firing conditions. In addition, firing under the above firing conditions can prevent excessive particle growth of the oxygen carrier. Until the above-mentioned firing temperature is reached, the temperature is increased at a rate of 1° C. / min to 20° C. / min, preferably 2° C. / min to 10° C. / min, which promotes the growth of oxygen carrier particles and also prevents the cracking of crystals (particles).

[0018] Alternatively, the oxygen carrier can be prepared as follows. First, oxides containing the metal elements constituting the oxygen carrier are mixed and pulverized. For pulverization, for example, a ball mill, a bead mill, a jet mill, a hammer mill, etc. can be used. In addition, this pulverization may be performed by either a dry method or a wet method. Next, the crushed aggregate is crushed and then calcined at a temperature of preferably 300° C. to 1200° C., more preferably 700° C. to 1000° C., for a time of preferably 1 hour to 24 hours, more preferably 1.5 hours to 20 hours. Thereafter, the fired mass is pulverized in the same manner as above to obtain the oxygen carrier.

[0019] The average particle size of the powdered oxygen carrier (including secondary particles) is not particularly limited, but is preferably from 1 μm to 100 μm, more preferably from 3 μm to 75 μm, and even more preferably from 5 μm to 50 μm. The average particle size of the oxygen carrier can be determined by acquiring volume-based particle size distribution data using a laser diffraction / scattering particle size distribution measuring device (e.g., "Partica LA-960" manufactured by Horiba, Ltd.) and processing the data. The measurement is usually performed in a wet manner.

[0020] <Latent heat storage particles> The latent heat storage particle has a core particle and a coating portion that coats at least a portion of the core particle.

[0021] [Core particle] The core particle is composed of an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound containing this element as a main component, and has a melting point of 100° C. or higher. Here, the "main component" refers to a component that accounts for 50% by mass or more of the entire core particle. Furthermore, by making the melting point of the components of the core particle 100° C. or higher, it is possible to prevent the core particle from melting when the coating portion is formed during the production of the latent heat storage particles. The core particles are preferably made of a phase change material (PCM) capable of utilizing the latent heat of solid-liquid phase change, particularly a phase change material having a heat of fusion of 150 J / g or more, in which case the core particles can secure a high amount of latent heat.

[0022] The components of the core particle may include, in addition to Al, elements with melting points lower than Al, such as Sn (melting point 232°C), In (melting point 157°C), Bi (melting point 272°C), Pb (melting point 328°C), Cd (melting point 321°C), and Cu (melting point 1085°C) with a melting point higher than Al. By using these components as the core particles of latent heat storage particles, it is possible to obtain latent heat storage particles having a different heat storage temperature from latent heat storage particles having core particles of Al or conventional Al alloys. In consideration of the environment, the component of the core particle is preferably a metal element selected from the group consisting of Al, Mg, Sn, Zn, Bi, In, and Cu, or an alloy containing these as a main component.

[0023] More preferred components of the core particles include Sn and Sn alloys mainly composed of Sn. By including Sn in the core particles, it is possible to easily obtain a PCM having a lower heat storage temperature (melting point) than a latent heat storage particle having an Al core particle. Examples of Sn alloys include Sn-Zn alloys, etc. The Zn content in the Sn-Zn alloy is preferably more than 0 mass% and less than 50 mass%, more preferably 20 mass% or less, and even more preferably 10 mass% or less. The core particle may be composed of Sn alone.

[0024] Another preferred component of the core particle is an alloy of Al and Si (Al-Si alloy). The content of Si in the Al-Si alloy is not particularly limited, and may be more than 0 mass% and less than 100 mass%, for example, 10 mass% to 90 mass%, or 10 mass% to 25 mass%. Yet another preferred component of the core particle is an Al alloy containing Cu and Si (Al-Cu-Si alloy). The contents of Cu and Si in the Al-Cu-Si alloy are not particularly limited, and it is sufficient that each of the contents of Cu and Si is more than 0 mass%, and the total content of Cu and Si is 90 mass% or less.

[0025] Yet another preferred component of the core particles is an alloy of Zn and Al (Zn-Al alloy). The content of Al in the Zn-Al alloy is not particularly limited, and may be more than 0 mass% and less than 100 mass%, or may be 50 mass% or less. As yet another preferred component of the core particle, the core particle may be composed of simple metallic Al with an Al content of 100 mass % without including any alloy component. Since it is desirable for the core particles to have a high melting point, the components of the core particles are preferably, in this order, Cu-Al-Si alloy, simple Al, Al-Ni alloy, and Al-Si alloy.

[0026] [Coating] The coating portion is made of at least one material selected from the group consisting of elements, alloys and inorganic compounds containing these elements, and mixtures thereof. The coating portion is different from the components of the core particles and does not react with the core particles or has poor reactivity with the core particles in the temperature range of the operating temperature of the reducing agent. Here, the components of the coating portion being poorly reactive with the core particles means that even if they react with the core particles, the product has a degree of reactivity with the core particles that does not affect the performance of the oxygen carrier. The operating temperature of the reducing agent is preferably in the range of 100°C to 1500°C. The above elements include elements selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd. The inorganic compounds include mixtures of two or more different inorganic compounds. The inorganic compounds include ceramics, glass, and α-Al by firing. 2 O 3Preferably, the alumina precursor is at least one selected from the group consisting of α-alumina precursors such as

[0027] As for ceramics, α-Al 2 O 3 , θ-Al 2 O 3 Alumina, such as SiO 2 (Silica) and the like. The α-alumina precursor can be converted to α-Al by, for example, firing at 880°C or higher. 2 O 3 Such α-alumina precursors include, for example, Al-containing compounds, Al-containing oxides, Al-containing hydroxides, AlOOH, Al(OH) 3 etc. The coating is made of Al, α-Al 2 O 3 , AlOOH, Al(OH) 3 and glass.

[0028] When the component of the core particle is a metal element or an alloy and the component of the coating portion is a ceramic, the metal contained in the core particle and the metal element contained in the ceramic that constitutes the coating portion may be the same or different. For example, if the component of the core particle is an Al alloy and the component of the coating portion is an Al oxide, the component of the coating portion is an oxide, which is different from the alloy that is the component of the core particle, but the metal Al contained in the component of the core particle and the metal element (Al) contained in the ceramic (oxide) that makes up the coating portion are the same. The thickness of the covering portion is not particularly limited, but is preferably 200 nm or more and 5 μm or less, and more preferably 1 μm or more and 2 μm or less.

[0029] The coating portion of the latent heat storage particle may cover at least a part of the surface of the core particle. The coverage rate of the coating portion on the surface of the core particle is preferably 50 area% or more, more preferably 70 area% or more, even more preferably 80 area% or more, particularly preferably 90 area% or more, and most preferably 100 area%. Therefore, the latent heat storage particles may have a dense shell formed by the coating portion tightly covering the core particle, or the coating portion may not tightly cover the core particle and exposed parts of the core particle may be scattered, or gaps (e.g., at the nano level) may be present due to the accumulation of child particles (hereinafter simply referred to as "child particles") that form the coating portion. Even if the core particles have exposed areas, gaps, etc., it is believed that deterioration of the core particles due to repeated use can be prevented or suppressed.

[0030] At least a part of the coating portion may have a particle shape. The particle shape of at least a part of the coating portion may be derived from the child particles used in producing the latent heat storage particles. The particle shape of at least a part of the coating portion can be confirmed regardless of whether or not the heat treatment described below is performed, and even if the heat treatment is performed, the particle shape can be confirmed at least in the outermost surface region of the coating portion. The particle shape of at least a part of the coating portion may be an aggregate of particles, and may be an aggregate of child particles used in producing the heat storage particles. Therefore, in the case of a latent heat storage particle, "at least a part of the coating portion is in a particulate shape" means that when the latent heat storage particle is observed with a scanning electron microscope at a magnification of 10,000 times, at least 10 particles of the coating portion (some of which may be joined to other particles) are confirmed.

[0031] The average particle size of the particulate coating portion is preferably 0.1 μm or more and 2 μm or less, and more preferably 0.2 μm or more and 1 μm or less. The average particle size refers to the average equivalent circle diameter of at least 10 particles in the coating portion observed under the above-mentioned electron microscope. When the particle-shaped portion of the coating portion having such a size bites into the oxygen carrier, it is possible to suitably prevent or suppress the oxygen carrier from being separated from the latent heat storage particle. In addition, at least a part of the region other than the particle-shaped region in the coating portion may be, for example, a porous or dense solid layer formed by melting and agglomerating child particles.

[0032] The average particle size of such latent heat storage particles is preferably 10 μm or more and 200 μm or less, more preferably 25 μm or more and 150 μm or less, and even more preferably 50 μm or more and 100 μm or less. In this case, the contact area between the oxygen carrier and the latent heat storage particles can be sufficiently increased, and therefore, heat exchange between the oxygen carrier and the latent heat storage particles can be smoothly performed. The average particle size of the latent heat storage particles can be measured in the same manner as the average particle size of the oxygen carrier.

[0033] The coating portion may contain a component of the core particle. That is, the coating portion may contain one or more components (core particle-derived components) selected from the group consisting of elements contained in the components of the core particle, alloys and inorganic compounds containing these elements, or mixtures thereof. In this case, the adhesion between the core particle and the coating portion can be improved. As mentioned above, the elements contained in the components of the core particle include elements selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd. Examples of the inorganic compound include ceramics containing the above elements and glasses containing the above elements. The component derived from the core particle contained in the coating portion may contain an element contained in the component of the core particle, and the form of the component derived from the core particle may be the same as or different from that of the component of the core particle. An example of a case in which the components of the core particle and the component derived from the core particle are in different forms is when the component of the core particle is a simple metal and the component derived from the core particle is an oxide of this metal.

[0034] The term "contains" the core particle-derived component in the coating portion means that at least a portion of the core particle-derived component is in contact with the component of the coating portion. For example, the entire core particle-derived component may be covered with the component of the coating portion, or a portion of the core particle-derived component may be covered with the component of the coating portion, with the remaining portion of the core particle-derived component being exposed to the outside air (for example, being in contact with a portion of the surface of the coating portion).

[0035] <Method of producing latent heat storage particles> Examples of methods for producing latent heat storage particles include a first method including a step of preparing core raw material particles of a specified component and child particles of a specified component, and a step of colliding the core raw material particles and the child particles using an impact method in a high-velocity air stream to perform hybridization by fixing the child particles to the surfaces of the core raw material particles; and a second method including a step of previously subjecting the surfaces of the core particles to a chemical conversion coating to form a primary coating, and a step of heat-treating this primary coating to form an oxide coating as a secondary coating on the surfaces of the core particles. According to these manufacturing methods, even when the core raw material particles are made of a PCM of a metal or alloy that does not contain Al, microencapsulation can be realized. Also, latent heat storage particles can be manufactured using PCMs with various heat storage temperatures as the core raw material particles. Furthermore, the surface of the core raw material particles can be easily coated with a component other than alumina, and latent heat storage particles with a coating component other than alumina can be easily manufactured. Each method will be described below.

[0036] [First method] [[Raw material particle preparation process]] As the raw material particles, core raw material particles and child particles for forming the coating portion are prepared. The core raw material particles are prepared to correspond to the core particles of the desired latent heat storage particles, for example, with an average particle diameter of 10 μm to 200 μm. The average particle diameter of the core raw material particles may be 100 μm or less, or 50 μm or less. Even if the core raw material particles contain fine particles with a particle diameter of less than 10 μm, relatively large core particles of, for example, about 30 μm can be obtained due to collisions between the fine particles during hybridization. The average particle size of the child particles is preferably 0.1 μm or more and 2 μm or less, and the ratio to the average particle size of the core raw material particles (average particle size of the child particles / average particle size of the core raw material particles) is preferably 0.001 or more and 0.2 or less. The average particle size of the child particles may be 1 μm or less, or may be 0.4 μm or less.

[0037] The components of the core raw material particles are the same as the components of the core particles of the latent heat storage particles, and are as described above for the components of the core particles of the latent heat storage particles. The components of the child particles are the same as the components (particularly the main components) of the coating portion of the latent heat storage particle, and are as described above for the components of the coating portion of the latent heat storage particle. In addition, if heat treatment is performed at a temperature equal to or higher than the melting point of the components of the core raw material particles after hybridization, or if melting and solidification are repeatedly performed by using a reducing agent, the components of the coating portion of the latent heat storage particle may be oxides of the components of the child particles, and the components of the coating portion of the latent heat storage particle may include oxides of the core raw material particles, as described above.

[0038] The blending ratio of the core material particles and the child particles to be fed into the apparatus is preferably such that the ratio of the child particles to the total of the core material particles and the child particles is 10% by volume or more and 50% by volume or less. The third component other than the core material particles and the child particles may include additives such as binders and antioxidants. The allowable amount of the third component may be 40% by volume or less when the amount of the child particles is 100% by volume.

[0039] [[Hybridization process]] In this process, core raw material particles and child particles are mechanically struck against the surfaces of the core raw material particles using a high-velocity airflow impact method, which is a dry mechanical method, to obtain latent heat storage particles in which child particles are fixed to the surfaces of the core raw material particles. Here, "adhesion" includes physical adhesion due to changes in the shape of the child particles, as well as adhesion due to chemical reactions between the core material particles and the child particles. The extent of coating (adhesion) is not particularly limited, and may be a part of the surface of the core particle. The higher the coverage of the coating portion on the surface of the core particle, the more preferable, and the specific details are as described above.

[0040] In the high-velocity airflow impact method, first, core material particles and child particles are supplied to an impact chamber through a sample inlet. As the rotor rotates, the core material particles and child particles in the impact chamber are scattered while rotating at high speed within the impact chamber, during which the child particles collide with the surfaces of the core material particles. At this time, some of the raw material particles enter the tube from one connection port of the circulation circuit connected to the collision chamber, circulate, and are then introduced back into the collision chamber from the other connection port. This circulation circuit allows the core raw material particles and the child particles to repeatedly collide with each other. By continuing the collision caused by rotation for a certain period of time in this manner, the child particles are fixed to the surfaces of the core raw material particles, and further the child particles are deformed to form coating portions, thereby obtaining latent heat storage particles.

[0041] During the collision between the core raw material particles and the child particles, the inlet path to the outlet is closed by the discharge valve, but after a certain period of time, the resulting latent heat storage particles are discharged from the outlet to the outside of the device through the inlet path to the outlet that is opened by moving the discharge valve. In order to prevent the inside of the collision chamber from becoming too hot, a cooling water passage may be provided and the collision process may be performed while cooling the inside of the collision chamber by flowing cooling water. According to the high-velocity air current impact method, latent heat storage particles can be produced regardless of the combination of the core raw material particle material and the child particle material. In addition, the latent heat storage particles can be obtained in a dry manner, without the need to use an organic solvent, and in a short time, so that the latent heat storage particles can be produced efficiently and stably.

[0042] The peripheral speed of the rotor in the above device is preferably 40 m / s or more and 100 m / s or less. The treatment time depends on the amount of the material to be treated, but is preferably from 1 minute to 120 minutes. The treatment temperature is preferably from room temperature to 70°C, and more preferably from room temperature to 50°C. The pressure and atmosphere of the collision chamber are not particularly limited. The atmosphere of the collision chamber can be, for example, an inert gas atmosphere such as an Ar atmosphere.

[0043] The latent heat storage particles obtained by hybridization may have a porous coating formed by aggregation of child particles, and at least a part of the coating, for example the outermost layer of the coating, has a particle shape. The latent heat storage particles obtained by hybridization do not necessarily need to be heat-treated (calcined). On the other hand, if necessary, the particles may be heat-treated for the purpose of reducing voids in the porous coating and forming a denser film as the coating.

[0044] [[Optional heat treatment (calcination)]] The heat treatment conditions, such as temperature and atmosphere, can be set according to the components of the core raw material particles and the desired coating portion. The heat treatment can be performed, for example, at a temperature equal to or higher than the melting point of the latent heat storage material, and can be performed, for example, at a temperature of 700° C. or higher depending on the melting point of the components of the core raw material particles. This heat treatment oxidizes the coating portion formed by the hybridization, and for example, a stronger aluminum oxide film can be formed. The aluminum oxide film formed by heat treatment is generally γ-Al at relatively low temperatures below 800℃. 2 O 3 The crystal form is α-Al, which is considered chemically stable at relatively high temperatures of about 880°C or higher (preferably 880°C or higher and 1230°C or lower). 2 O 3 It is obtained in the crystalline form of When the core raw material particles are, for example, an Al-Si alloy, the heat treatment is preferably performed at a temperature of 900° C. to 1230° C. On the other hand, when the core raw material particles are, for example, Sn, the Sn burns at about 600° C. in an oxidizing atmosphere, and therefore the heat treatment is preferably performed at a temperature lower than 600° C.

[0045] The atmosphere for the heat treatment is not particularly limited, but examples thereof include an air atmosphere, and an oxygen atmosphere adjusted by supplying oxygen gas to a heat treatment furnace. The temperature inside the furnace is increased using a heater, and once the temperature of the sample reaches a predetermined temperature, heat treatment (oxidation treatment) is performed for, for example, 3 hours or more and 5 hours or less, to obtain heat-treated latent heat storage particles. Specifically, the heat treatment can be carried out, for example, by filling a crucible with the latent heat storage particles obtained by the above-mentioned hybridization, setting the crucible in a heat treatment furnace equipped with a heater, and placing a thermocouple attached to the tip of an insertion rod at the top of the crucible.

[0046] [Second Method] [[Chemical conversion treatment process]] As the raw material particles, for example, core raw material particles containing Al are prepared. For the core raw material particles, particles having an average particle diameter of, for example, 10 μm or more and 200 μm or less can be prepared according to the core particles of the intended latent heat storage particles. The average particle diameter of the core raw material particles may be 100 μm or less, or may be 50 μm or less. The aluminum component on the surface of the core particle reacts with water molecules to form aluminum oxide hydrate (Al 2 O 3 H 2 O) is formed, which becomes the primary coating. The excess hydrogen becomes gas.

[0047] [[Oxide coating process]] By heat treating the primary coating, an oxide coating is formed as a secondary coating on the surface of the core particle. In this heat treatment, the primary coating, hydrated aluminum oxide (Al 2 O 3H 2 O), water molecules dissociate to form crystalline aluminum oxide (Al 2 O 3 At the same time, the aluminum component on the surface of the core particle reacts with oxygen to form crystalline aluminum oxide (Al 2 O 3 ) The heat treatment conditions, such as temperature and atmosphere, can be set according to the components of the core raw material particles and the intended coating portion. The heat treatment can be performed at a temperature equal to or higher than the melting point of the latent heat storage particles, for example, at a temperature of 700°C or higher according to the melting point of the components of the core raw material particles.

[0048] <Method of producing reducing agent> The reducing agent can be produced, for example, by the following first and second methods. <<First Method>> The oxygen carrier and the latent heat storage particles as described above are mixed in a predetermined mixing ratio, and then molded and fired to obtain a reducing agent as a fired molded product. Specifically, the method for producing a reducing agent includes a mixing step of mixing raw materials to produce a mixture, a molding step of molding the mixture to produce a molded body, and a firing step of firing the molded body to produce a fired product.

[0049] [Mixing process] Latent heat storage particles in an amount of 1 part by mass or more and 60 parts by mass or less are mixed with 100 parts by mass of the oxygen carrier. In order to impart physical properties suitable for molding, water may be further mixed in. Examples of water include ion-exchanged water, pure water, distilled water, tap water, etc. In order to improve the plasticity, shape retention, homogeneity, etc. of the molded body, an organic or inorganic binder may be further mixed. There is no limitation on the order in which these raw materials are mixed.

[0050] For kneading the above raw materials, a kneader such as an internal kneader, a single-screw or twin-screw extruder, or an open roll type kneader can be used. There are no particular limitations on the type of kneader, and kneaders that can be used include container rotation types that rotate containers such as cylindrical, V-shaped, and double cone-shaped containers, fixed container types that enable powder to be kneaded using a fixed rotating shaft, horizontal axis rotation types, vertical axis rotation types, and vibration rotation types.

[0051] [Molding process] The method for forming the mixture is not particularly limited as long as it is a method capable of forming a fired product into a molded body having a shape suitable for a fixed-bed reactor. Examples of the molding method include compression molding, extrusion molding, injection molding, tablet molding, spray granulation, fluidized bed granulation, rolling granulation, etc. Among these, extrusion molding is preferred as the molding method from the viewpoint of realizing a high pore volume, a high specific surface area, and a high production volume. For the extrusion molding of the mixture, for example, a screw type molding machine, a roll type molding machine, a piston type molding machine, or the like can be used. In addition, during molding, the molded body may be cut with a cutter to make the length uniform, and the molded body after cutting may be further cut. Also, the molded body after cutting may be granulated into a shape close to a sphere using a marumerizer.

[0052] [Firing process] The sintering of the molded body is preferably carried out in an air atmosphere. Moreover, the temperature (sintering temperature) when sintering the molded body is preferably from 200° C. to 1200° C., more preferably from 400° C. to 1000° C., and further preferably from 600° C. to 950° C. By sintering the molded body within this temperature range, it is possible to prevent or suppress changes in the crystal structure of the oxygen carrier, so that the performance of the reducing agent (oxygen carrier) can be maintained and the mechanical strength of the reducing agent can be finished within an appropriate range.

[0053] <<Second Method>> A predetermined amount of latent heat storage particles is added during the production of the oxygen carrier to prepare a reducing agent in a particulate (powdered) form, which is then molded and fired to obtain a reducing agent in the form of a fired molded body. The method for producing the particulate reducing agent is not particularly limited, but examples thereof include the sol-gel method, co-precipitation method, solid phase method, and hydrothermal synthesis method. As an example, it can be prepared as follows. First, a salt of a metal element constituting the oxygen carrier is dissolved in water to prepare an aqueous solution. Next, a predetermined amount of latent heat storage particles is added to this aqueous solution. After that, this aqueous solution is gelled by heating, and then dried and fired. That is, the particulate reducing agent can be easily and reliably prepared by the so-called sol-gel method. In addition, for preparing the aqueous solution, acidic water adjusted to be acidic with, for example, citric acid, acetic acid, malic acid, tartaric acid, hydrochloric acid, nitric acid, or a mixture thereof may be used.

[0054] The conditions for the sol-gel method can be the same as those explained in the above <Method for Producing Oxygen Carrier>. The conditions for molding and firing the particulate reducing agent may be the same as those described in the [Molding step] and [Firing step] in the above <Production method of reducing agent>.

[0055] The reducing agent is preferably a fired product of a molded body having a circular bottom surface with a diameter of 2 mm to 10 mm, or a fired product of a spherical molded body with a diameter of 2 mm to 10 mm. By using a reducing agent having a size equal to or larger than the above lower limit, it is possible to prevent the pressure loss during the chemical looping reaction from becoming too large, thereby enabling stable operation. In addition, by using a reducing agent having a size equal to or smaller than the above upper limit, it is possible to increase the filling efficiency of the reducing agent into the reaction tube, thereby improving the conversion efficiency of the reducing gas and the oxidizing gas. In addition, a reducing agent having the above size can also ensure a sufficient contact area with the reducing gas and the oxidizing gas. The diameter is preferably 2.5 mm or more and 6 mm or less, and more preferably 3 mm or more and 5 mm or less.

[0056] In the reducing agent, the oxygen carrier contains Ce and Zr or contains Fe, and in the latent heat storage particles, the component of the core particle contains Al, and the component of the coating portion is Al. 2 O 3 The oxygen carrier is a composite oxide containing Ce, Zr and Fe or an oxide containing Fe, and in the latent heat storage particles, the component of the core particle is simple Al, and the component of the coating portion is Al. 2 O 3 It is more preferable that the oxygen carrier has a suitable degree of distortion in the crystal lattice, and can smoothly and reliably transfer oxygen elements between the oxygen carrier and the counter substance. On the other hand, the latent heat storage particles have excellent heat storage properties, and can smoothly exchange heat with the oxygen carrier. This reduces the temperature change of the reducing agent (oxygen carrier), thereby suppressing the deterioration of the performance and life of the oxygen carrier. In addition, since the temperature change of the reducing agent is reduced, the thermal energy input to the reducing agent from the outside can be reduced, and the temperature control (heat control) of the reducing agent can be simplified.

[0057] The content of the latent heat storage particles in the reducing agent is preferably 1% by mass or more and 60% by mass or less, more preferably 1% by mass or more and 40% by mass or less, even more preferably 1% by mass or more and 20% by mass or less, particularly preferably 3% by mass or more and 17.5% by mass or less, and most preferably 5% by mass or more and 15% by mass or less. By making it equal to or more than the above lower limit, the latent heat amount of the reducing agent can be increased, so that the reaction heat generated by the oxygen carrier can be sufficiently absorbed by the latent heat storage particles. By making it equal to or less than the above upper limit, the content of the oxygen carrier can be prevented from becoming too small, and the conversion efficiency of the reducing gas and the oxidizing gas per volume can be improved. That is, within the above range, the oxygen carrier and the latent heat storage particles can exhibit their performance in a well-balanced manner.

[0058] The crushing strength of the reducing agent is preferably 1N or more and 40N or less, more preferably 1N or more and 30N or less, even more preferably 1.5N or more and 20N or less, and particularly preferably 2N or more and 15N or less. By making it equal to or more than the lower limit, it is possible to prevent or suppress the powdering of the reducing agent when it is filled into the reaction tube and the powdering during the chemical looping reaction, and therefore it is possible to stably operate the gas production device (system). In addition, by making it equal to or less than the upper limit, it is possible to prevent the size change caused by the expansion and contraction during the oxidation and reduction of the oxygen carrier from becoming too large, so that the decomposition of the latent heat storage particles and the powdering of the compact are unlikely to occur. That is, within the above range, it is possible to stably generate gas while preventing the decomposition and deterioration of the latent heat storage particles during the use of the reducing agent (for example, during gas generation by the chemical looping method). In addition, it is possible to prevent the oxygen carrier and the latent heat storage particles from becoming too dense, and to sufficiently ensure their performance.

[0059] The bulk density of the reducing agent is 0.1 g / cm 3 More than 5g / cm 3 It is preferable that the concentration is 0.3 g / cm or less. 3 More than 4g / cm 3 More preferably, it is 0.5 g / cm or less. 3 More than 3g / cm 3 It is more preferable that the temperature is equal to or lower than the above-mentioned lower limit. By making the temperature equal to or higher than the above-mentioned lower limit, the oxygen carrier and the latent heat storage particles can be sufficiently contacted with each other, and thus the effect of heat control (heat exchange) is improved. By making the temperature equal to or lower than the above-mentioned upper limit, a high efficiency of gas diffusion into the inside of the reducing agent can be maintained, and thus the conversion efficiency of the reducing gas and the oxidizing gas is improved. In other words, within the above-mentioned range, it is possible to sufficiently achieve both the effect of temperature control and the performance of gas conversion efficiency during the use of the reducing agent (for example, during gas generation by the chemical looping method).

[0060] The cumulative specific surface area of ​​the reducing agent measured by mercury intrusion porosimetry is 3 m 2 / g or more, and the cumulative pore volume is 0.1 cm 3 / g or more. Such a reducing agent has a fine structure and can increase the number of reaction sites with the gas it comes into contact with. This makes it possible to sufficiently increase the conversion efficiency of carbon dioxide to carbon monoxide and the conversion efficiency of hydrogen to water. The cumulative specific surface area is 3m 2 / g or more 55m 2 / g or less, and 2 / g or more 50m 2 / g or less is more preferable, and 7.5m 2 / g or more 45m 2 / g or less. This makes it possible to increase the number of reaction sites with the gas that the reducing agent (oxygen carrier) comes into contact with while maintaining the mechanical strength and durability of the reducing agent. This makes it possible to increase the conversion efficiency from carbon dioxide to carbon monoxide and the conversion efficiency from hydrogen to water, and also to prevent a decrease in lifespan.

[0061] The cumulative pore volume is 0.1 cm 3 / g or more 2.5cm 3 / g or less, and 0.2 cm 3 / g or more 2cm 3 / g or less is more preferable, and 0.3 cm 3 / g or more 1.5cm 3 More preferably, it is 0.4 cm 3 / g or more 1cm 3 It is particularly preferable that the pore volume is less than 1 / g. If the pore volume is too small, the raw material gas and the reducing gas are difficult to penetrate into the inside of the reducing agent. As a result, the contact area between the reducing agent and the raw material gas and the reducing gas is reduced, and the conversion efficiency of carbon dioxide to carbon monoxide by the oxygen carrier and the regeneration efficiency of the oxygen carrier in the oxidized state by the reducing gas are likely to decrease.

[0062] <Other ingredients> The reducing agent may contain an organic binder and / or an inorganic binder to the extent that the above-mentioned effects are not impaired. Examples of the inorganic binder include aluminum hydroxide, alumina sol, silica sol, zirconium oxyhydroxide, zirconia sol, alumina, silica, zirconia, silicon carbide, boron nitride, and zeolite. On the other hand, examples of the organic binder include polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, starch, and polyethylene oxide.

[0063] [How to use the reducing agent] The reducing agent can be used, for example, in a chemical looping process, as described above, and can also be used in applications in which carbon dioxide is reduced by contact to produce carbon monoxide (carbon value), as described above. More specifically, it is preferable to carry out a reduction reaction of carbon dioxide and a reduction reaction of a reducing agent, and it is preferable to use the reducing agent so as to circulate between the reduction reaction of carbon dioxide and the reduction reaction of the reducing agent. Note that in the reduction reaction of the reducing agent, a reducing gas containing other reducing substances is used.

[0064] The reducing agent is preferably used in the so-called reverse water gas shift reaction. The reverse water gas shift reaction is a reaction that produces carbon monoxide and water from carbon dioxide and hydrogen. When the chemical looping method is applied, the reverse water gas shift reaction is carried out separately into a reduction reaction of the reducing agent (first process) and a reduction reaction of carbon dioxide (second process), where the reduction reaction of the reducing agent is the reaction shown in the following formula (A), and the reduction reaction of carbon dioxide is the reaction shown in the following formula (B).

[0065] H 2 (Gas) + MO x (Solid) → H 2 O(gas) + MO x-1 (solid) (A) CO 2 (Gas) + MO x-1 (solid) → CO(gas) + MO x (Solid) (B) In the formulas (A) and (B), x is usually 2. That is, in the reduction reaction of the reducing agent, hydrogen, which is a type of reducing substance, is oxidized to produce water, and in the reduction reaction of carbon dioxide, carbon dioxide is reduced to produce carbon monoxide, which is a type of carbon valuable.

[0066] The reaction temperature (contact temperature with the reducing gas) in the reduction reaction of the reducing agent may be any temperature at which the reduction reaction can proceed, but is preferably a temperature above 500° C., more preferably 600° C. or higher, even more preferably 700° C. or higher, and particularly preferably 750° C. or higher. Within this temperature range, the reduction reaction of the reducing agent can proceed efficiently. The upper limit of the reaction temperature is preferably 1050° C. or less, more preferably 1000° C. or less, even more preferably 950° C. or less, particularly preferably 900° C. or less, and most preferably 850° C. or less. By setting the upper limit of the reaction temperature within the above range, it is possible to improve economic efficiency. The lower limit and the upper limit can be combined in any manner to define the reaction temperature range.

[0067] In addition, during the reduction reaction of the reducing agent, the amount of hydrogen (reducing gas) to be brought into contact with the reducing agent in an oxidized state is preferably 1 mmol to 50 mmol per 1 g of the reducing agent, more preferably 2.5 mmol to 35 mmol, and even more preferably 5 mmol to 20 mmol. The reducing agent has a high hydrogen utilization rate because oxygen elements can smoothly enter and leave the reducing agent. Therefore, the reducing agent is sufficiently reduced (regenerated) with a small amount of hydrogen. This reduces the energy required to generate hydrogen, and also contributes to reducing the amount of carbon dioxide generated when obtaining energy. The hydrogen utilization rate (%) is a value expressed as a percentage of the amount of carbon monoxide produced (number of moles) relative to the amount of hydrogen (number of moles) brought into contact with 1 g of reducing agent.

[0068] Furthermore, the reaction temperature in the reduction reaction of carbon dioxide (contact temperature with the oxidizing gas) is preferably a temperature exceeding 500° C., more preferably 600° C. or higher, further preferably 700° C. or higher, and particularly preferably 750° C. or higher. Within this temperature range, the reduction reaction of carbon dioxide can proceed efficiently. The upper limit of the reaction temperature is preferably 1050° C. or less, more preferably 1000° C. or less, even more preferably 950° C. or less, particularly preferably 900° C. or less, and most preferably 850° C. or less. The reducing agent can perform the reduction reaction of carbon dioxide to carbon monoxide with high efficiency even at low temperatures, so that the reduction reaction of carbon dioxide can be set at a relatively low temperature. Furthermore, by setting the upper limit of the reaction temperature in the above range, not only can waste heat be easily utilized, but also further economic efficiency can be improved. The lower limit and the upper limit can be combined in any manner to define the reaction temperature range.

[0069] In addition, during the reduction reaction of carbon dioxide, the amount of carbon dioxide brought into contact with the reducing agent is preferably 1 mmol to 50 mmol per 1 g of the reducing agent, more preferably 2.5 mmol to 30 mmol, and even more preferably 5 mmol to 20 mmol. The reducing agent allows the smooth transfer of oxygen elements. Therefore, the reducing agent has a high carbon dioxide conversion rate (hence, a large amount of carbon monoxide is produced), and from this viewpoint as well, it contributes to the reduction of carbon dioxide. On the other hand, since the reduction reaction is efficiently carried out by a reducing gas containing hydrogen, the reducing agent can be regenerated with a small amount of hydrogen. The amount of carbon monoxide produced in the reducing agent is preferably about 0.3 mmol or more and 1 mmol or less per gram of the reducing agent.

[0070] In this embodiment, the reduction product (carbon valuable product) obtained by the reduction reaction of carbon dioxide contains carbon monoxide, but may contain other substances other than carbon monoxide, or may be a mixture of carbon monoxide and other substances. A specific example of the other substances is methane. It is preferable that the reduction products such as carbon monoxide obtained by the reduction reaction of carbon dioxide are further converted into organic substances by microbial fermentation or the like. Examples of microbial fermentation include anaerobic fermentation. Examples of the organic substances obtained include methanol, ethanol, acetic acid, butanol, derivatives thereof, or mixtures thereof, and compounds of C5 or more such as isoprene. Furthermore, the reduced products such as carbon monoxide may be converted by metal oxides, etc., into C1 to C20 compounds including hydrocarbons and alcohols that are conventionally synthesized by petrochemistry. Specific compounds that can be obtained include methane, ethane, propylene, methanol, ethanol, propanol, acetaldehyde, diethyl ether, acetic acid, butyric acid, diethyl carbonate, butadiene, etc.

[0071] According to the above embodiment, by including latent heat storage particles, during the hydrogen to water conversion reaction (endothermic reaction) by the oxygen carrier, the core particles of the latent heat storage particles change from a liquid phase to a solid phase to provide the oxygen carrier with latent heat (heat of solidification), and during the carbon dioxide to carbon monoxide conversion reaction (endothermic or exothermic reaction), the core particles of the latent heat storage particles change from a solid phase to a liquid phase to absorb and store the heat generated by the oxygen carrier. This reduces the temperature change of the reducing agent (oxygen carrier), and thus suppresses the deterioration of the performance and life of the oxygen carrier. In addition, because the temperature change of the reducing agent is reduced, the thermal energy input to the reducing agent from the outside can also be reduced, and the temperature control (heat control) of the reducing agent can also be easily simplified. In this way, the reducing agent can withstand repeated use at high temperatures, allowing for more efficient conversion of carbon dioxide to carbon monoxide (carbon values) through chemical looping reactions at high temperatures. Furthermore, it may be provided in the following aspects:

[0072] (1) A reducing agent which generates oxygen vacancies when it comes into contact with a reducing gas containing hydrogen and which eliminates the oxygen vacancies when it comes into contact with an oxidizing gas containing carbon dioxide, the reducing agent comprising an oxygen carrier having oxygen ion conductivity and latent heat storage particles, the oxygen carrier containing at least two of the metal elements belonging to Groups 3 and 4 of the periodic table, including lanthanides and actinides, or containing Fe, the latent heat storage particles having a core particle and a coating portion which coats at least a part of the core particle, the components of the core particle being Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd. and a component of the coating portion is at least one selected from the group consisting of an element, an alloy or a compound mainly composed of the element, and has a melting point of 100°C or higher. The component of the coating portion does not react with the core particle or has poor reactivity with the core particle in a temperature range of the operating temperature of the reducing agent, and is different from the component of the core particle. The coating portion is at least one selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof. The content of the latent heat storage particles in the reducing agent is 1% by mass or more and 60% by mass or less. The crushing strength of the reducing agent is 1 N or more and 40 N or less. The bulk density of the reducing agent is 0.1 g / cm. 3 More than 5g / cm 3 The cumulative specific surface area of ​​the reducing agent measured by mercury intrusion porosimetry using a mercury porosimeter is 3 m or less. 2 / g or more, and the cumulative pore volume is 0.1 cm 3 / g or more of a reducing agent.

[0073] (2) In the reducing agent described in (1) above, the oxygen carrier contains Ce and Zr or contains Fe, and in the latent heat storage particles, the component of the core particle contains Al, and the component of the coating portion is Al. 2 O 3 A reducing agent comprising:

[0074] (3) In the reducing agent described in (1) or (2) above, the average particle diameter of the latent heat storage particles is 10 μm or more and 200 μm or less, and the reducing agent is a sintered product of a molded body having a circular bottom surface with a diameter of 2 mm or more and 10 mm or less, or a sintered product of a spherical molded body with a diameter of 2 mm or more and 10 mm or less.

[0075] (4) The reducing agent according to any one of (1) to (3) above, wherein at least a part of the coating portion is in a particulate form, and the particulate coating portion has an average particle diameter of 0.1 μm or more and 2 μm or less.

[0076] (5) The reducing agent according to any one of the above (1) to (4), wherein the coating portion contains a component of the core particle.

[0077] (6) The reducing agent according to any one of the above (1) to (5), wherein the contact with the reducing gas is carried out at a temperature exceeding 500°C.

[0078] (7) The reducing agent according to any one of the above (1) to (6), wherein the contact with the oxidizing gas is carried out at a temperature exceeding 500°C. Of course, this is not the case.

[0079] As described above, various embodiments of the present invention have been described, but these are presented as examples and do not limit the scope of the invention in any way. The novel embodiments can be embodied in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. The embodiments and modifications thereof are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims.

[0080] For example, the reducing agent of the present invention may have any other additional configuration compared to the above-mentioned embodiment, may be replaced with any configuration that exhibits a similar function, or some of the configurations may be omitted. In the above embodiment, a gas containing hydrogen has been described as a representative reducing gas, but the reducing gas may also be a gas containing at least one selected from hydrocarbons (e.g., methane, ethane, acetylene, etc.) and ammonia as a reducing substance in addition to hydrogen. EXAMPLES

[0081] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. 1. Oxygen Carrier Fabrication As precursors of oxygen carriers, the following compounds were prepared. (Oxygen carrier precursor) Cerium(III) nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 98.0%) Zirconium nitrate dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 97.0%) Samarium nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.5%) Copper(II) nitrate trihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.0%) Iron(III) nitrate nonahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9%)

[0082] (Oxygen Carrier 1) First, predetermined amounts of cerium (III) nitrate hexahydrate, zirconium nitrate dihydrate, copper (II) nitrate trihydrate, iron (III) nitrate nonahydrate, and samarium nitrate hexahydrate were each weighed out. Next, 6.06 g of citric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.5%) was weighed and dissolved in 96 mL of deionized water to obtain an aqueous citric acid solution. After that, the precursor (metal nitrate salt) was added to the aqueous citric acid solution at room temperature while stirring to prepare an aqueous precursor solution. After 30 minutes had elapsed, 2.15 g of ethylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.5%) was added to the aqueous precursor solution, and the temperature was raised to 80°C.

[0083] The temperature was maintained at 80° C. with continuous stirring until a viscous gel was formed, after which the gel was transferred to a drying oven. The gel was dried at 120°C for 5 hours. The resulting swollen mass of organic and inorganic compounds was pulverized and heated from room temperature to 450°C at a rate of 8°C / min in an air atmosphere, and then fired at 450°C for 4 hours.Then, the temperature was further raised to 950°C at a rate of 8°C / min, and then fired at 950°C for 8 hours. Finally, the fired mass was mechanically pulverized to obtain oxygen carrier 1. The oxygen carrier 1 was particles having an average particle size of 10 μm.

[0084] (Oxygen Carrier 2) Oxygen carrier 2 was produced in the same manner as oxygen carrier 1, except that cerium (III) nitrate hexahydrate and zirconium nitrate dihydrate were each weighed and used in a predetermined amount. Note that oxygen carrier 2 was a particle having an average particle size of 10 μm. (Oxygen Carrier 3) Oxygen carrier 3 was produced in the same manner as oxygen carrier 1, except that a predetermined amount of iron (III) nitrate nonahydrate was weighed and used. Oxygen carrier 3 was particles having an average particle size of 10 μm.

[0085] 2. Preparation of latent heat storage particles First, core raw material particles containing Al and having an average particle size of 30 μm or less were prepared. Next, 1 g of aluminum hydroxide was weighed and dissolved in 100 mL of deionized water to obtain an aqueous aluminum hydroxide solution, which was then heated and stirred at 100° C. for 1 hour. Next, the core raw material particles were added to an aluminum hydroxide aqueous solution and stirred while being heated at 100°C for 3 hours. This treatment resulted in the formation of α-Al on the surface of the core particles. 2 O 3A primary coating of aluminum oxide, which is the precursor of the above, was formed. Next, the aqueous solution was filtered to recover the core particles on which the primary coating was formed, and the core particles were then transferred to a drying furnace. Drying was carried out at 120°C for 12 hours. Thereafter, the temperature was raised from room temperature to 1200°C at a rate of 10°C / min in an air atmosphere, and the core particles on which the primary coating was formed were then fired at 1200°C for 3 hours. In this way, the primary coating was heat-treated to form an oxide coating as a secondary coating on the surface of the core particles, and latent heat storage particles were obtained.

[0086] A scanning electron microscope (SEM) image of the obtained latent heat storage particles is shown in Figure 1. Figure 1(b) is an enlarged image of the scanning electron microscope (SEM) image shown in Figure 1(a). Figure 2 shows the measurement results of the latent heat storage particles by X-ray diffraction (XRD), and Figure 3 shows the measurement results of the latent heat storage particles by differential scanning calorimetry (DSC). Figure 3(a) is a graph showing the change in heat flow when the latent heat storage particles are heated, and Figure 3(b) is a graph showing the change in heat flow when the latent heat storage particles are cooled. From the SEM image shown in FIG. 1, it was confirmed that the core particle and at least a part of the core particle were covered with a covering portion (shell), and that at least a part of the latent heat storage particle was in contact with the oxygen carrier. From the XRD measurement results shown in Figure 2, it was confirmed that metal Al, which is a component of the core particles, and aluminum oxide, which is a component of the coating portion, coexist with the oxygen carrier. In addition, from the DSC curve obtained by differential scanning calorimetry shown in Figure 3, it was confirmed that the latent heat storage particles have a heat of fusion L of 201 J / g and a melting point Tm of 660°C. Since the majority of the latent heat storage particles are core particles, the melting point Tm of the latent heat storage particles is substantially equal to the melting point Tm of the core particles.

[0087] 3. Preparation of Reducing Agent Example 1 A mixture was prepared by mixing 90 parts by mass of oxygen carrier 1, 10 parts by mass of latent heat storage particles, and an appropriate amount of ion-exchanged water and polyvinyl alcohol. A disk-shaped molded body was produced by extrusion molding using this mixture. The molded body was then baked at 650°C for 4 hours in an air atmosphere to produce a reducing agent. The diameter of the bottom surface of the resulting reducing agent was 5 mm. Figure 4(a) shows a photograph of the appearance of the reducing agent obtained in Example 1. Example 2 A mixture was prepared by mixing 90 parts by mass of oxygen carrier 2, 10 parts by mass of latent heat storage particles, and an appropriate amount of ion-exchanged water and polyvinyl alcohol. A disk-shaped molded body was produced by extrusion molding using this mixture. The molded body was then baked at 650°C for 4 hours in an air atmosphere to produce a reducing agent. The diameter of the bottom surface of the resulting reducing agent was 5 mm. Figure 4(b) shows a photograph of the appearance of the reducing agent obtained in Example 2.

[0088] Example 3 First, predetermined amounts of cerium (III) nitrate hexahydrate and zirconium nitrate dihydrate were each weighed out. Next, a predetermined amount of citric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.5%) was weighed and dissolved in 200 mL of deionized water to obtain an aqueous citric acid solution. After that, the precursor (metal nitrate salt) was added to the aqueous citric acid solution at room temperature while stirring to prepare an aqueous precursor solution. After 30 minutes had passed, a predetermined amount of ethylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.5%) and latent heat storage particles were added to the precursor aqueous solution so that the amount contained therein was 10 parts by mass per 100 parts by mass of the resulting particulate reducing agent. The temperature of the aqueous precursor solution was then increased to 80° C. The temperature was maintained at 80° C. with continuous stirring until a viscous gel was formed, after which the gel was transferred to a drying oven. The gel was dried at 120°C for 5 hours.

[0089] The resulting swollen mass of organic and inorganic compounds was pulverized and heated from room temperature to 450°C at a rate of 10°C / min in an air atmosphere, and then fired at 450°C for 4 hours.Then, the temperature was further raised to 700°C at a rate of 10°C / min, and then fired at 700°C for 4 hours. Finally, the calcined mass was mechanically pulverized to obtain the reducing agent in particle form. The reducing agent in the form of particles was used to produce a disk-shaped compact by tableting. The compact was then fired at 650°C for 4 hours in an air atmosphere to produce the reducing agent. The diameter of the bottom surface of the resulting reducing agent was 3 mm.

[0090] Example 4 A reducing agent was produced in the same manner as in Example 3, except that the amount of latent heat storage particles added to the precursor aqueous solution was changed so that the amount contained in 100 parts by mass of the resulting particulate reducing agent was 30 parts by mass. The diameter of the bottom surface of the resulting reducing agent was 3 mm. Example 5 A reducing agent was produced in the same manner as in Example 3, except that the amount of latent heat storage particles added to the precursor aqueous solution was changed so that the amount contained in 100 parts by mass of the resulting particulate reducing agent was 60 parts by mass. The diameter of the bottom surface of the resulting reducing agent was 3 mm.

[0091] Example 6 A reducing agent was prepared in the same manner as in Example 5, except that a predetermined amount of iron (III) nitrate nonahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity: 99.9%) was weighed and used. The diameter of the bottom surface of the resulting reducing agent was 3 mm. Example 7 A mixture was prepared by mixing 40 parts by mass of oxygen carrier 2, 60 parts by mass of latent heat storage particles, and an appropriate amount of ion-exchanged water and polyvinyl alcohol. A disk-shaped molded body was produced by extrusion molding using this mixture. Then, the molded body was baked at 650°C for 4 hours in an air atmosphere to produce a reducing agent. The diameter of the bottom surface of the resulting reducing agent was 3 mm.

[0092] Comparative Example 1 Except for changing extrusion molding to tablet molding, a reducing agent was produced in the same manner as in Example 1. The diameter of the bottom surface of the resulting reducing agent was 6 mm. (Reference example 1) Except for omitting the latent heat storage particles, a reducing agent was produced in the same manner as in Example 1. The diameter of the bottom surface of the resulting reducing agent was 5 mm. (Reference example 2) Instead of latent heat storage particles, Al with an average particle size of 3 μm 2 O 3 Except for using particles, a reducing agent was produced in the same manner as in Example 1. The diameter of the bottom surface of the resulting reducing agent was 5 mm.

[0093] (Reference example 3) Except for omitting the latent heat storage particles, a reducing agent was produced in the same manner as in Example 2. The diameter of the bottom surface of the resulting reducing agent was 5 mm. (Reference example 4) Instead of latent heat storage particles, Al with an average particle size of 3 μm 2 O 3 Except for using particles, a reducing agent was produced in the same manner as in Example 2. The diameter of the bottom surface of the resulting reducing agent was 5 mm. (Reference example 5) Instead of latent heat storage particles, Al with an average particle size of 3 μm 2 O 3 A reducing agent was produced in the same manner as in Example 7, except that particles were used. The diameter of the bottom surface of the resulting reducing agent was 3 mm.

[0094] 4. Measurement and Evaluation 4-1.X-ray diffraction measurement (XRD) Before performing X-ray diffraction measurements, samples of the objects to be measured were prepared. First, about 100 mg of the measurement object was weighed out into a mortar and crushed with a pestle. After that, the measurement object was evenly filled into the hole in the sample filling section of the sample plate, and the surface of the sample plate and the surface of the measurement object were adjusted to be flush with each other. For the X-ray diffraction measurements, an X-ray diffractometer (PANanalytical, "AREIS") was used, and measurements were performed using the focusing method. A ceramic tube was used as the target cathode, and characteristic X-rays of CuKα (Kα1 wavelength (λ) = 1.54056 Å (0.154056 nm), Kα2 wavelength (λ) = 1.54439 Å (0.154439 nm), Kα2 ratio = 0.50000) were used for diffraction. The diffractometer was set with a divergence slit of 1 / 2°, a divergence longitudinal limiting slit of 10 mm, a scattering slit of 2°, and a receiving slit of 0.15 mm. The goniometer radius was 145 mm.

[0095] Then, the prepared sample was irradiated with X-rays under conditions of a tube voltage of 40 kV and a tube current of 15 mA. The measurement was performed with the goniometer scanning angle set to a range of 10° to 90.5°, a scanning speed of 3.5° / min, and a measurement step of 0.01. The measurement was performed in air at room temperature. After the measurement, the data obtained without separation of Kα1 and Kα2 was analyzed. Data was analyzed using software (PANanalytica, High Score). The results of measurement by X-ray diffraction (XRD) for each of the Examples, Comparative Examples, and Reference Examples are shown in FIGS. As shown in FIGS. 5 to 10, it was found that the target reducing agents were obtained in Examples 1 to 6, Comparative Example 1, and Reference Examples 1 to 5.

[0096] 4-2.Differential scanning calorimetry (DSC) The prepared latent heat storage particles were subjected to differential scanning calorimetry using a differential scanning calorimeter (manufactured by Hitachi High-Tech Science Corporation, "DSC7200"). First, the latent heat storage particles were weighed out as the measurement object in a mortar and crushed with a pestle. After that, 10 mg of the crushed measurement object was used for the measurement. The measurement was performed under the conditions of increasing the temperature from 50°C to 700°C at 5°C / min in a nitrogen gas atmosphere, and then decreasing the temperature from 700°C to 50°C at 5°C / min.

[0097] 4-3. Particle size distribution measurement (wet method) The particle size distribution was measured using a laser diffraction / scattering particle size distribution measuring device ("Partica LA-960" manufactured by Horiba, Ltd.) in a wet flow cell. The flow cell was made of synthetic quartz, the light source was a semiconductor laser (650 nm) of 5 mW and an LED (405 nm) of 3 mW, and the detector was a ring-shaped silicon photodiode. The measurements were performed at a temperature of 25° C. and a humidity of 20%, on a dispersion liquid prepared by dispersing about 10 mg of the target object in about 180 mL of purified water (pH 6.8 to 7.2). The measurement was carried out at least three times, and the median particle diameters obtained from each particle size distribution measurement were averaged to obtain the average particle diameter.

[0098] 4-4. Scanning Electron Microscope (SEM) - Energy Dispersive X-ray Spectroscopy (EDX) Measurement A cross section along the thickness direction of the reducing agent obtained in Example 2 was observed at a magnification of 300 times using a SEM-EDX device (manufactured by Hitachi High-Tech Science Corporation, "S-4800"), with an acceleration voltage in the range of 1.0 kV to 15 kV. FIG. 11 shows an SEM image and an element mapping image of a cross section along the thickness direction of the reducing agent obtained in Example 2.

[0099] 4-5.Scanning electron microscope (SEM) images Cross sections along the thickness direction of the reducing agents obtained in Example 2 and Comparative Example 1 were photographed using a scanning electron microscope (manufactured by Hitachi High-Tech Science Corporation, "S-4800"). Fig. 12 is an SEM image taken at a magnification of 30 times of a cross section along the thickness direction of the reducing agent obtained in Example 2. In the SEM image shown in Fig. 12, the white spots are latent heat storage particles, and it was confirmed that they were uniformly dispersed in the oxygen carrier and were not decomposed or deteriorated. Fig. 13 is an SEM image taken at a magnification of 1000 times of a cross section along the thickness direction of the reducing agent obtained in Comparative Example 1. In the SEM image shown in Fig. 13 (area surrounded by a white circle), decomposition (cracks, fissures) of the latent heat storage particles was confirmed.

[0100] 4-6. Measurement of crushing strength The crushing strength of the reducing agents obtained in each of the Examples and Comparative Examples was measured in accordance with JIS Z 8841 (1993). Specifically, an LTS-50NB manufactured by MinebeaMitsumi Inc. was used to measure the strength in the direction perpendicular to the bottom surface of the reducing agent.

[0101] 4-7. Measurement of cumulative specific surface area and cumulative pore volume The cumulative specific surface area and cumulative pore volume were measured by measuring the pore size distribution of the reducing agent using a mercury intrusion method with a mercury porosimeter. Specifically, a Poremaster manufactured by Quantachrome was used, and the measurement was performed using a sample (reducing agent) of 0.1 g to 3.0 g. The measurement range was pore diameter 0.0036 μm to 400 μm, the surface tension of mercury was 480 dyn / cm, the contact angle was 140°, the cell size was 10 mmφ×3 cm, and the measurement cell volume was 0.5 cc.

[0102] 4-8. Measurement of bulk density The bulk density was measured in accordance with JIS R 1634: 1998. Specifically, the measurement was performed for one particle of the reducing agent, and the measurement was performed at least 10 times, and the average value of the values ​​obtained in each measurement was taken as the bulk density.

[0103] 4-9.Evaluation of temperature change of reducing agent 14 and 15 are conceptual diagrams showing the configuration of a device (reactor 1 or reactor 2) for evaluating the temperature change of the reducing agent. (Reactor 1) In Examples 1, 2, and 7, Comparative Example 1, and Reference Examples 1 to 5, first, as shown in FIG. 14, a stainless steel reaction tube having an inner diameter of 43 mm and a length of 750 mm was prepared, and the stainless steel reaction tube was filled with quartz glass wool to a height of 10 mm to 30 mm, and further filled with the reducing agent obtained in each example to a height of 150 mm. Thermocouples were placed in the reaction tube to measure three temperatures: the inlet gas temperature (T1), the temperature in the oxygen carrier layer (T2), and the outlet gas temperature (T3). The following evaluations were performed while the reaction tube was placed in an electric furnace and heated, and the temperatures listed below were the set temperatures of the electric furnace.

[0104] (Reactor 2) In Examples 3 to 6, first, as shown in FIG. 15, a quartz reaction tube with an inner diameter of 23 mm was prepared, and quartz balls were placed in the reaction tube to a height of 25 mm. The reducing agent obtained in each example was then placed in the reaction tube to a height of at least 25 mm, and the remaining portion was filled with quartz balls again. Thermocouples were placed in the reaction tube to measure the seven temperatures: inlet gas temperature (T1), oxygen carrier layer temperatures (T2 to T5), and outlet gas temperatures (T6, T7). The following evaluations were performed while the reaction tube was placed in an electric furnace and heated, and the temperatures listed below were the set temperatures of the electric furnace.

[0105] ((Evaluation of Temperature Changes of Reducing Agents Obtained in Examples 1 and 2, Comparative Example 1, and Reference Examples 1 to 4)) In the reactor 1 filled with the reducing agent obtained in Examples 1 and 2, Comparative Example 1, and Reference Examples 1 to 4, first, the reducing agent was heated to 600°C at a heating rate of 10°C / min while flowing nitrogen gas at a flow rate of 1000 mL / min, and then heated at the same temperature for 60 minutes to stabilize the temperature. Next, in order to activate the oxygen carrier, hydrogen gas (reducing gas) was flowed at a flow rate of 1000 mL / min for 40 minutes to carry out a reduction reaction of the oxygen carrier. After the oxygen carrier was reduced, carbon dioxide gas (oxidizing gas) was flowed at a flow rate of 1000 mL / min for 20 minutes. Thereafter, nitrogen gas was passed at a flow rate of 1000 mL / min for 30 minutes for gas exchange. In this manner, activation of the reducing agent was completed.

[0106] Next, while flowing nitrogen gas at a flow rate of 1000 mL / min, the reducing agent was heated to 620°C at a heating rate of 10°C / min and heated at the same temperature for 60 minutes to stabilize the temperature. Furthermore, hydrogen gas (reducing gas) was flowed at a flow rate of 1000 mL / min for 40 minutes. Thereafter, carbon dioxide gas (oxidizing gas) was flowed at a flow rate of 1000 mL / min for 20 minutes to carry out an oxidation reaction of the oxygen carrier, thereby oxidizing the oxygen carrier. Next, hydrogen gas (reducing gas) was flowed at a flow rate of 1000 mL / min for 40 minutes to carry out a reduction reaction of the oxygen carrier, thereby reducing the oxygen carrier.

[0107] At this time, the temperature T2 at the center of the reducing agent in the height direction, the temperature T1 100 mm above it (a position above the reducing agent), and the temperature T3 100 mm below it (a position below the quartz glass wool) were each continuously measured. The results for the reducing agents obtained in Examples 1 and 2 and Reference Examples 1 to 4 are shown in FIG. 16 and FIG. Fig. 16 is a graph showing the evaluation results of temperature changes of the reducing agents obtained in Example 1, Reference Examples 1 and 2. Fig. 17 is a graph showing the evaluation results of temperature changes of the reducing agents obtained in Example 2, Reference Examples 3 and 4.

[0108] ((Evaluation of temperature changes of reducing agents obtained in Example 7 and Reference Example 5)) In the reactor 1 filled with the reducing agent obtained in Example 7 and Reference Example 5, first, the reducing agent was heated to 700°C at a heating rate of 10°C / min while flowing nitrogen gas at a flow rate of 1000 mL / min, and then heated at the same temperature for 60 minutes to stabilize the temperature. Next, in order to activate the oxygen carrier, hydrogen gas (reducing gas) was flowed at a flow rate of 1000 mL / min for 20 minutes to carry out a reduction reaction of the oxygen carrier. After the oxygen carrier was reduced, carbon dioxide gas (oxidizing gas) was flowed at a flow rate of 1000 mL / min for 20 minutes. Thereafter, nitrogen gas was passed at a flow rate of 1000 mL / min for 30 minutes for gas exchange. In this manner, activation of the reducing agent was completed.

[0109] Next, the reducing agent was cooled to 620°C at a rate of 10°C / min while flowing nitrogen gas at a flow rate of 1000mL / min, and heated at the same temperature for 60 minutes to stabilize the temperature. Furthermore, hydrogen gas (reducing gas) was flowed at a flow rate of 1000mL / min for 15 minutes. After that, nitrogen gas was flowed at a flow rate of 1000mL / min for 15 minutes for gas exchange. Next, carbon dioxide gas (oxidizing gas) was flowed at a flow rate of 1000 mL / min for 30 minutes to carry out an oxidation reaction of the oxygen carrier, thereby oxidizing the oxygen carrier. At this time, the temperature T2 at the center of the reducing agent in the height direction, the temperature T1 100 mm above it (a position above the reducing agent), and the temperature T3 100 mm below it (a position below the quartz glass wool) were each continuously measured.

[0110] ((Evaluation of temperature changes of reducing agents obtained in Examples 3 to 6)) In the reactor 2 filled with the reducing agent obtained in Examples 3 to 6, first, while flowing argon gas at a flow rate of 1000 mL / min, the reducing agent was heated to 600°C at a heating rate of 10°C / min, and then heated at the same temperature for 30 minutes to stabilize the temperature. Next, in order to activate the oxygen carrier, argon gas was flowed at a flow rate of 500 mL / min and hydrogen gas (reducing gas) was flowed at a flow rate of 500 mL / min for 5 minutes to carry out a reduction reaction of the oxygen carrier. After the oxygen carrier was reduced, argon gas was flowed at a flow rate of 500 mL / min and carbon dioxide gas (oxidizing gas) was flowed at a flow rate of 500 mL / min for 5 minutes. Thereafter, argon gas was passed at a flow rate of 1000 mL / min for 5 minutes for gas exchange. In this manner, activation of the reducing agent was completed.

[0111] Next, while flowing argon gas at a flow rate of 1000 mL / min, the reducing agent was heated to 620°C at a heating rate of 10°C / min and heated at the same temperature for 60 minutes to stabilize the temperature. Furthermore, argon gas at a flow rate of 500 mL / min and hydrogen gas (reducing gas) at a flow rate of 500 mL / min were flowed for 2 minutes or more. Thereafter, argon gas was flowed at a flow rate of 1000 mL / min for 5 minutes for gas exchange. Thereafter, argon gas at a flow rate of 500 mL / min and carbon dioxide gas (oxidizing gas) at a flow rate of 500 mL / min were flowed for 2 minutes or more to carry out an oxidation reaction of the oxygen carrier, thereby oxidizing the oxygen carrier. At this time, temperatures T1 to T6 at six points along the height direction of the reducing agent and a temperature T7 at the bottom end of the quartz ball were each measured consecutively.

[0112] 4-10. Measurement of carbon monoxide production (evaluation of reducing agent characteristics) The amount of carbon monoxide produced by the reducing agent was measured by the following procedure using a rapid catalyst evaluation system equipped with a fixed-bed flow-type reactor and a quadrupole mass spectrometer directly connected to the reactor. Specifically, a quartz reaction tube having an inner diameter of 6 mm was prepared, and the reducing agent was filled in such a manner that the filling amount became 0.5 g. Next, while flowing helium gas at a flow rate of 10 mL / min, the temperature was raised to 650°C at a heating rate of 15°C / min, and heated at the same temperature for 5 minutes to stabilize the temperature. Next, in order to activate the oxygen carrier, hydrogen gas (reducing gas) was flowed at a flow rate of 10 mL / min for 10 minutes to carry out a reduction reaction (first process) of the oxygen carrier, thereby reducing the oxygen carrier. At this time, the gas discharged from the outlet contained water vapor. After that, for gas exchange, helium gas was passed at a flow rate of 10 mL / min for 5 minutes, and then carbon dioxide gas was passed at a flow rate of 10 mL / min for 10 minutes to carry out the reduction reaction of carbon dioxide (second process) and reduce the carbon dioxide gas (raw material gas). At this time, the product gas discharged from the exhaust port contained carbon monoxide.

[0113] Next, for this test, the following process was carried out. First, for gas exchange, helium gas was flowed at a flow rate of 10 mL / min for 5 minutes. Next, hydrogen gas (reducing gas) was flowed at a flow rate of 10 mL / min for 4 minutes to carry out the reduction reaction of the oxygen carrier (first process), thereby reducing the oxygen carrier. At this time, the gas discharged from the outlet contained water vapor. After that, for gas exchange, helium gas was passed through at a flow rate of 10 mL / min for 5 minutes, and then carbon dioxide gas was passed through at a flow rate of 10 mL / min for 5 minutes to carry out the reduction reaction of carbon dioxide (second process) and reduce the carbon dioxide gas (raw material gas). At this time, the product gas discharged from the exhaust port contained carbon monoxide.

[0114] In the above process, the temperature of the reducing agent was maintained at 650° C. and the process was carried out under atmospheric pressure conditions when any of the gases was flowed. As performance, the amount of carbon monoxide produced (mmol / g) per unit mass of the oxygen carrier contained in the packed reductant was calculated. The amount of carbon monoxide produced (mmol / g) per unit mass of the oxygen carrier was calculated during the period in which the carbon dioxide conversion rate was maintained at 5% or more after the start of flowing carbon dioxide gas (feed gas). Here, the carbon dioxide conversion rate is a value calculated by the following formula. Carbon dioxide conversion rate (%) = (amount of carbon monoxide detected per unit second) ÷ (amount of carbon monoxide detected per unit second + amount of carbon dioxide detected per unit second) × 100

[0115] The measurement results and evaluation results in Examples 1, 2, and 7 and Comparative Example 1 are shown in Table 1 below. The evaluation of the temperature change of the reducing agent was performed according to the following criteria. ○: In the case of the oxygen carrier containing Ce, when carbon dioxide gas (oxidizing gas) is passed through the oxygen carrier, the difference in maximum temperature reached is 10°C or more compared to the case of the oxygen carrier alone (Reference Example 1 or Reference Example 3), and no decomposition or deterioration of the latent heat storage particles is observed. In addition, in the case of the oxygen carrier containing Fe, when hydrogen gas (reducing gas) is passed through the oxygen carrier, the difference in maximum temperature reached is 10°C or more compared to the case of the oxygen carrier alone (Reference Example 1 or Reference Example 3), and no decomposition or deterioration of the latent heat storage particles is observed. 2 O 3 Compared to the case where particles are included (Reference Example 5), the difference in the minimum attainable temperature is 5° C. or more, and no decomposition or deterioration of the latent heat storage particles is observed. ×: In the case of the oxygen carrier containing Ce, when carbon dioxide gas (oxidizing gas) was passed through the oxygen carrier alone (Reference Example 1 or Reference Example 3), the difference in maximum temperature reached was less than 10°C, and decomposition (cracks, fissures) of the latent heat storage particles was confirmed. In addition, in the case of the oxygen carrier containing Fe, when hydrogen gas (reducing gas) was passed through the oxygen carrier, ... 2 O 3 Compared with the case where particles were included (Reference Example 5), the difference in the minimum attained temperature was less than 5° C., and decomposition or deterioration of the latent heat storage particles was confirmed.

[0116] The measurement results and evaluation results in Examples 3 to 6 are also shown in Table 1 below. The evaluation of the temperature change of the reducing agent was performed according to the following criteria. ○: In the temperature change at any point of the temperature of the reducing agent or quartz ball (T2 to T5), the temperature swing width calculated from the difference between the maximum and minimum temperatures reached when hydrogen gas (reducing gas) and carbon dioxide gas (oxidizing gas) are flowed is less than 30°C, and no decomposition or deterioration of the latent heat storage particles is confirmed. ×: In the temperature change at any point of the temperature of the reducing agent or quartz ball (T2 to T5), the temperature swing calculated from the difference between the maximum and minimum temperatures reached when hydrogen gas (reducing gas) and carbon dioxide gas (oxidizing gas) were flowed was 30°C or more, and decomposition or deterioration of the latent heat storage particles was confirmed.

[0117] The amount of carbon monoxide produced was measured according to the following standards. ○: The amount of carbon monoxide produced per unit mass (mmol / g) of the oxygen carrier in the reducing agent containing latent heat storage particles is equal to or greater than that of the oxygen carrier in the reducing agent not containing latent heat storage particles (Reference Example 1, Reference Example 3, or Reference Example 5). ×: The amount of carbon monoxide produced (mmol / g) per unit mass of the oxygen carrier in a reducing agent containing latent heat storage particles is less than that in the case of an oxygen carrier in a reducing agent not containing latent heat storage particles (Reference Example 1, Reference Example 3, or Reference Example 5).

[0118] [Table 1]

Claims

1. A reducing agent which generates oxygen vacancies when contacted with a reducing gas containing hydrogen and which eliminates the oxygen vacancies when contacted with an oxidizing gas containing carbon dioxide, The oxygen carrier has oxygen ion conductivity, and the latent heat storage particles are contained. The oxygen carrier contains at least two of the metal elements belonging to groups 3 and 4 of the periodic table, including lanthanides and actinides, or contains Fe; The latent heat storage particle has a core particle and a coating portion that coats at least a portion of the core particle, The component of the core particle is an element selected from the group consisting of Al, Mg, Si, Ti, Fe, Ni, Cu, Zn, Sn, Sb, Ga, In, Bi, Pb, and Cd, or an alloy or compound containing the element as a main component, and has a melting point of 100° C. or higher; a component of the coating portion does not react with the core particle or has poor reactivity with the core particle in a temperature range of an operating temperature of the reducing agent, is different from a component of the core particle, and is at least one selected from the group consisting of an element, an alloy and an inorganic compound containing the element, and a mixture thereof; The content of the latent heat storage particles in the reducing agent is 1% by mass or more and 60% by mass or less, The reducing agent has a crushing strength of 1 N or more and 40 N or less, The bulk density of the reducing agent is 0.1 g / cm 3 5g / cm or more 3 is as follows: The cumulative specific surface area of ​​the reducing agent measured by pore size distribution measurement using a mercury intrusion method using a mercury porosimeter is 3 m 2 / g or more, and the cumulative pore volume is 0.1 cm 3 / g or more.

2. The reducing agent according to claim 1 , The oxygen carrier comprises Ce and Zr or comprises Fe; In the latent heat storage particles, the core particle contains Al, and the coating portion contains Al. 2 O 3 A reducing agent comprising:

3. The reducing agent according to claim 1 , The average particle diameter of the latent heat storage particles is 10 μm or more and 200 μm or less, The reducing agent is a sintered product of a molded body having a circular bottom surface with a diameter of 2 mm or more and 10 mm or less, or a sintered product of a spherical molded body with a diameter of 2 mm or more and 10 mm or less.

4. The reducing agent according to claim 1 , At least a part of the coating portion is in a particle shape, The reducing agent, wherein the average particle diameter of the particulate coating portion is 0.1 μm or more and 2 μm or less.

5. The reducing agent according to claim 1 , The coating portion includes a component of the core particle.

6. The reducing agent according to claim 1 , The contact with the reducing gas occurs at a temperature above 500° C.

7. The reducing agent according to claim 1 , The contact with the oxidizing gas is at a temperature above 500° C.

Citation Information

Patent Citations

  • Automatically controlling method for plate thickness

    JP1983058926A

  • Reductant

    JP2021049489A

Cited By

  • Method for producing methanation catalyst, methanation catalyst, method for synthesizing methane, and cell for synthesizing methane

    JP7784584B1